2003
DOI: 10.2174/1389557033487908
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Synthesis of Acetylcholinesterase Inhibitors

Abstract: The acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities of a series of pyrano[2,3-b]quinolines (2, 3), [1,8]naphthyridines (5, 6), 4-amino-2,3-diaryl-5,6,7,8-tetrahydrofuro[2,3-b]quinolines (11-13)/ 4-amino-6,7,8,9-tetrahydro-2,3-diphenyl-5H-cyclohepta[e]furo[2,3-b]pyridine (14), 4-amino-5,6,7,8-tetrahydro-2,3-diphenylthieno[2,3-b]quinoline (15)/ 4-amino-6,7,8,9-tetrahydro-2,3-diphenyl-5H-cyclohepta[e]thieno[2,3-b]pyridine (16) are described. These compounds are tacrine analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Some quinoline based compounds showed also antineoplastics, antiasthmatic and antiplatelet activity [5][6][7][8][9][10]. The acetylcholinesterase inhibitory activity of various quinoline derivatives has been tested for potential treatment of nervous diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some quinoline based compounds showed also antineoplastics, antiasthmatic and antiplatelet activity [5][6][7][8][9][10]. The acetylcholinesterase inhibitory activity of various quinoline derivatives has been tested for potential treatment of nervous diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many quinoline derivatives have shown anti-cholinesterase activity and can be potential agents for treatment of AD (12)(13)(14). Gatta et al in 1992(15) reported the synthesis of THQs derivatives as potential AChEI, Fink et al in 1995(16) reported the synthesis and evaluation of 5-amino-5,6,7,8-tetrahydroquinolinones as AChEI, and in 2012 Maalej et al (17)reported the synthesis, biological assessment, and molecular modeling of racemic 7-aryl-9,10,11,12-tetrahydro-7H-benzo [7,8]chromeno [2,3-b]quinolin-8-amines as potential drugs for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholinesterase (AChE) inhibitors such as tacrine (1a) and donepezil by ''cholinergic hypothesis'' have been a useful and practical treatment for AD [5,6]. Moreover, the interest for AChE inhibitors has been greatly renewed due to the recent evidences that AChE might function to accelerate b-amyloid peptide (Ab) formation and could play a role during amyloid deposition in AD brain [7,8].…”
Section: Introductionmentioning
confidence: 99%